Heterofermentative lactic acid bacteria such as Limosilactobacillus as a strong inhibitor of aldehyde compounds in plant-based milk alternatives - Sugahara, Hirosuke; Kato, Sayaka; Nagayama, Keitaro; Sashihara, Koichi; Nagatomi, Yasushi (Frontiers in Sustainable Food Systems, 2022)
Reduction of greenhouse gas emissions is important to limit climate change. Because ruminant animals emit greenhouse gases, the worldwide plant-based alternative market is an emerging trend for eating less meat and dairy products. To produce plant-based dairy products such as yogurt alternatives, certain lactic acid bacterial species, which are used for cow’s milk fermentation, are often used. Substrate changes from cow’s milk to plant-based milk caused nutritional changes, and unsaturated fatty acids are more enriched in plant-based milk alternatives than in cow’s milk. Unsaturated fatty acids can lead to the formation of aldehydes, some of which are off-flavors; therefore, substrate changes have the potential to alter the suitable lactic acid bacterial species used for fermentation to control flavor formation, such as aldehyde compounds. However, differences in the effect of the fermentation processes on aldehyde compounds have not been evaluated among lactic acid bacterial species. In this study, we comprehensively evaluated the effect of lactic acid bacterial fermentation on aldehyde compounds in synthetic medium and plant-based milk alternatives using 20 species of lactic acid bacteria. Heterofermentative lactic acid bacteria such as strains belonging to Limosilactobacillus had a strong aldehyde-reducing ability, likely from differences in alcohol dehydrogenase function. Because the odor detection threshold of ethanol compounds was lower than that of their equivalent aldehyde compounds, our findings are valuable for the fermentation of plant-based milk alternatives with lactic acid bacteria with the goal of decreasing off-flavors derived from aldehyde compounds.